FAKTOR-FAKTOR PENYEBAB SISWA YANG TIDAK DISIPLIN DI SEKOLAH - Hermatasiyah, Nur (JIEGC Journal of Islamic Education Guidance and Counselling, 2022)
This study aims to reveal the internal and external factors that cause students to violate discipline at school. This research includes descriptive research, meaning research that describes a situation as it is. The total population of this study were students who committed disciplinary violations at SMP Negeri 19 Jambi City, amounting to 106 students. From the total population that has been described, so that this study is representative. Then all members of the population is the sample of this study or totaling sampling. Data obtained from the results of filling out questionnaires by respondents, the questionnaire totaled 38 items with two yes and no answers. The results of filling out the questionnaire were analyzed by using percentage data analysis techniques, and using interpretation criteria. Based on the results of the study, it was revealed that the factors that caused students' discipline violations from internal were habits 8.51%, behavior 10.73%, interests 8.41%, values and morals 16.21%. While from the external, namely the family environment 11.89%, relationships with friends 7.18%, school environment 4.86%, and subjects 9.03%. In accordance with the results of the study, it is hoped that all relevant parties can anticipate disciplinary violations in schools. Various forms of assistance and guidance can be provided to students, especially from the parents.